TRANSPORTASI KERETA API SCS (SEMARANG CHERIBON STOOMSTRAM MAATSCHAPPIJ) DI KABUPATEN KENDAL PADA TAHUN 1897-1930 - Mirza (Siginjai: Jurnal Sejarah, 2023)
Kendal Regency became part of the rail transportation network when one of the colonial private railroad companies from Zustermaatschappij, namely SCS (Semarang Cheribon Stoomstram Maatschappij), was built through the area. The companies and railroads that were built at the end of the 19th century seem to have been based on certain factors of interest. Through descriptive qualitative research using historical research methods, it can be seen that initially SCS was founded as a small rail transportation (tram) to accommodate passengers in the western region of Semarang, until then it expanded into industrial commodity transportation. This can be seen from the connection between the main railway line and the track leading to the factory. Even in Kendal Regency, SCS built a new route outside the main route to shorten the travel time to Semarang. Towards the era of the economic depression and the aftermath of the impact of the First World War, the condition of SCS rail transportation experienced ups and downs. Even so, as the only engine transportation in Kendal Regency, this train was still running amidst the onslaught of the unstable economic conditions at that time.